The use of Indonesian Slang by English Education Department students in their daily communication - Asmira, Mira (Maliki Interdisciplinary Journal, 2024)
One of the language styles used by Millennials is slang, Slang becomes the part of language variation because of the need to adapt to new or different aspects of society and factor of social prestige. the purposes of this study to find out what types of slang words that students usually use. This study uses descriptive research method with the paradigm of experimental design. The researcher took the audio recordings, wrote the transcript of conversation, and analysing the extract of conversation .The researchers took their own friends as the subject of the research. The result of this study is several types of Indonesian Slang vocabulary which is the responden use in daily communication.